Gastroprotektivna uloga ekstrakta kore žute kepok banane (Musa k Paradisiaca L. var. Kepok) i uticaj na markere oksidativnog stresa: malondialdehida i azot oksida - Samiasih, Amin; Khoiriyah, Khoiriyah; Ethica, Stalis Norma; Sulistyaningtyas, Ayu Rahmawati; Pranata, Satriya; Vanchapo, Antonius Rino (Scripta Medica, 2023)
Background/Aim: Flavonoids, tannins, saponins and polyphenols in yellow kepok banana (Musa x paradisiaca L. var. kepok) peel potentially could be a solution for peptic ulcer prevention. This study aims to prove the efficacy of kepok banana peel extract as gastroprotective by analysing the number of gastric ulcers and through markers of oxidative stress - malondialdehyde (MDA) and nitric oxide (NO). Methods: The study was performed on 33 female Wistar rats aged 3-4 months, weighed 100-250 g. Rats were divided into 3 groups: Musa Paradisiaca Var Kepok 1 (MPVK1) treatment group, Musa Paradisiaca Var Kepok 2 (MPVK2) and control group (K). In MPVK1 a dose of kepok banana peel extract at a dose of 80 mg / 200 g body weight (BW) was given and the MPVK 2 group dose was 160 mg / 200 g BW. The gastritis induction was performed by using 5 % acetylsalicylic acid at a dose of 1500 mg/kg BW. MDA examination by HPLC method, NO examination by ELISA method and macroscopic examination by counting the number of ulcers on the gastric mucosa was performed. Results: The results showed that the lowest average MDA level was in the MPVK2 group which was 3.27, whereas the highest average NO level was in the MPVK2 group 286.17. The highest mean number of ulcers was in the control group at 3.55. By analysing all the results it can be concluded that there is a significant difference in the average levels of MDA (p = 0.013), NO (p < 0.001) and the number of ulcers (p < 0.001) of the three groups. Conclusion: Banana peel extract was proven to be effective as a gastroprotective through markers of MDA, NO and the number of ulcers in Wistar rats.
Keywords: Kora banane; Malondialdehid; Azot oksid; Gastroprotekcija